Rights of Prisoners from Human Rights Perspectives: a Select Study of Women Prisoners in India - Avnish Bhatt, Mr.; Rajesh Bahuguna, Prof Dr. (International Journal of Engineering and Technology, 2019)
Women play a vital role in society. The important role she plays is the ability of the mother. The constitution of India confers the status of equality to women in India. It also imposes on the State the obligation to protect women's rights and to comply with the requirements of international conventions on women's rights. But if we talk about the dark side of this, then, in reality, women in prison face a series of problems, even their basic human rights are ignored, despite a series of Supreme Court, High Court and commission recommendations different. It creates difficulties in the prison that require special attention and must be eliminated. Women's prisoners in Indian prisons are fewer. It could be neglecting the rights of women prisoners. The main objective of this research is to highlight the problems of women prisoners, the violation of the human rights of women prisoners, the condition of women's prisons, list the human rights and constitutional rights of women prisoners and suggest necessary changes.Â